Flexural capacity of fiber reinforced polymer sea sand seawater concrete: reliability analysis and calibration of partial factor - Yi, Shixiang; Tang, Zhongping; Liu, Xiang; Chen, Hao (Frontiers in Materials, 2025)
Due to its efficient use of marine resources, seawater sea-sand concrete (SWSSC) has emerged as a promising sustainable building material and has garnered significant interest. At the same time, fiber reinforced polymer (FRP) materials show great potential for application in SWSSC structures owing to their excellent mechanical properties and corrosion resistance. However, the behavior of SWSSC is more uncertain compared to conventional concrete, which affects the reliability of structural members in terms of load-bearing capacity. To ensure the safety and reliability of FRP-SWSSC members, a database of 49 flexural tests on FRP-reinforced SWSSC beams was compiled to characterize the statistical distribution of the concrete material and the error associated with the computational model. Based on this data, a reliability analysis was conducted and a reliability model was developed. The partial factors were calibrated according to the target reliability index, resulting in recommended values of 1.4 for the Chinese code, 1.6 for ACI, 1.5 for CSA, and 1.3 for Eurocode.